Distribution of Schmallenberg Virus and Seroprevalence in Belgian Sheep and Goats. Issue 5 (10th January 2013) - Méroc, E.; De Regge, N.; Riocreux, F.; Caij, A. B.; van den Berg, T.; van der Stede, Y.
Summary A serological survey to detect Schmallenberg virus (SBV)‐specific antibodies by ELISA was organized in the Belgian sheep population to study the seroprevalence at the end of the epidemic. One thousand eighty‐two sheep samples which were collected from 83 herds all over Belgium between November 2011 and April 2012 were tested. The overall within‐herd seroprevalence and the intraclass correlation coefficient were estimated at 84.31% (95% CI: 84.19–84.43) and 0.34, respectively. The overall between‐herd seroprevalence was 98.03% (95% CI: 97.86–98.18). A spatial cluster analysis identified a cluster of six farms with significantly lower within‐herd seroprevalence in the south of Belgium compared with the rest of the population (P = 0.04). It was shown that seroprevalence was associated to flock density and that the latter explained the presence of the spatial cluster. Additionally, 142 goat samples from eight different herds were tested for SBV‐specific antibodies. The within‐herd seroprevalence in goats was estimated at 40.68% (95% CI: 23.57–60.4%). The results of the current study provided evidence that almost every Belgian sheep herd has been in contact with SBV during 2011 and should be taken into consideration as part of comprehensive SBV surveillance and control strategies.